Designing Learning Monitoring snd Evaluation Management Systems for Lecturer Performance in Informatics Study Program: (Case Study : Universitas Sarjanawiyata Tamansiswa) - Eka Yulia Sari; Titik Rahmawati; Dina Yulina Heriyani (Journal of Information Technology and Its Utilization, 2022)
The main responsibilities of a lecturer is to transform, to develop and to transfer knowledge through teaching and learning process. Assessment by students for their lecturers to provide input for lecturers and study program quality is needed so that the teaching and learning process can be controlled and in accordance with the established quality standards. In carrying out the process of monitoring and evaluating on lecturer performance, the Informatics Study Program, Faculty of Engineering, Universitas Tamansiswa is currently using Google form to distribute questionnaires. This is considered ineffective and produces invalid data. Therefore, the use of technology can be a solution to this problem. The purpose of this research is to design a management information system model for monitoring and evaluating learning that can facilitate the software development stage. The design of this learning monitoring and evaluation processing system uses the Unified Modeling Language (UML) model. While the software development method proposed by the author is Agile Software Development. The result of this research is a design model with UML in the form of use case diagrams, activity diagrams, and class diagrams, where the results of this design model can facilitate the next stage of software development. In addition, PIECES analysis is used to assist in identifying weaknesses in the current system to facilitate the mapping of system requirements. Needs mapping is used to identify the proposed new system, in which this proposed new system has 4 user levels, namely: administrator, GMP (Gugus Mutu Prodi), lecturers and students. Each user has its own authority in the proposed system.